High technology trade, innovation and economic growth : evidence from aggregate and disaggregate trade products - Lam, Leonard Fong Litt; Siong, Hook Law; W. N. W. Azman-Saini; M. S. M. Khair-Afham; Lim, Thye Goh (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study evaluates the effect of high-technology trade on economic growth in an emerging economy, using quarterly data from 1990 until 2018. The role of innovation in moderating the high technology trade - economic growth nexus also emphasize. The empirical findings based on the autoregressive distributed lag (ARDL) approach reveal that high-tech trade, foreign direct investment and physical capital stock are statistically significant determinants of economic growth. The innovation must be presence to support or moderate the effect of high-tech industry on economic growth. Moving into subsector, the findings indicate that the development of machinery and transport equipment, mineral fuels and lubricants, manufactured goods and chemical sectors are crucial as the niche areas of focus for policy design and resource allocation. The results are robust using the fully modified ordinary least squares (FMOLS) estimation.